Feasibility Study on Hemotransfusion Transmission of West Nile Fever Virus in the Territory of the Saratov Region - E. V. Kazorina; T. Yu. Krasovskaya; E. V. Naidenova; A. V. Kazantsev; E. N. Kalinina; E. A. Fedotov; S. A. Shcherbakova (Проблемы особо опасных инфекций, 2015)
In order to identify the risk of hemotransfusion transmission of West Nile virus in the territory of the Saratov Region, carried out has been analysis of 1760 blood sera and 270 blood samples from donors residing in the Region, intended to detect markers, indicating recent infection with the virus. Consequently, identified have been IgM and/or low-avid IgG suggestive of a late contact with the agent. The data obtained demonstrate the feasibility of realization of hemotransfusion mechanism for West Nile virus transmission in the territory of the Saratov Region in a particular season. It is planned to continue investigations, applying 2 analytical methods: ELISA and PCR, with individual testing of biological material from each donor.